THU0016 Trans-Ethnic Genome-Wide Analysis Reveals MHC Variability in Rheumatoid Arthritis Genetic Susceptibility. (9th June 2015) - Teruel, M.; Martin, J.E.; Rodriguez-Rodriguez, L.; Balsa, A.; Pascul-Salcedo, D.; Gonzalez-Alvarez, I.; Ortiz, A.M.; Acevedo-Vazquez, E.M.; Cardiel, M.H.; Esquivel-Valerio, J.A.; Maradiaga-Ceceña, M.A.; Musuruana, J.L.; et al.
Abstract : Background: Previous trans-ethnic meta-analysis including samples from European and Asian individuals support the hypothesis that the genetic component of rheumatoid arthritis is shared. However, our knowledge about populations such as the native population of Americans, also called Amerindians or Native Americans, is poor. Few genetic studies have been conducted in Amerindian populations. Objectives: We conducted a meta-analysis of Latin American, with Amerindian-European (primarily South European) admixed individuals and Spanish, in order to find new risk loci for RA susceptibility shared and specific for each one of them. Methods: A total of 5, 533 subjects were genotyped with the immunochip custom array and included in the final data set. The OR of the meta-analysis of both populations was performed using the inverse variance method under fixed-effects model. The imputation process of the MHC region was performed with a dense reference panel using the Beagle software. Results: We confirm the association in this population at genome-wide significant level of the HLA and PTPN22 . The MCH analysis showed that four amino acids in positions 11, 13, 70 and 86 of the HLA-DRβ1 explain all the association in our combined analysis. Interestingly, we observed differential associations in each cohort separately. In the Spanish cohort, only amino acids 13 and 86 of HLA-DRβ1 were necessary to explain all the association in the MHC region, while for the Latin American population, amino acids at positions 13 and 70 were the important ones. Outside of the HLA region, the most interesting signals observed were on 2p25.3, 3q25.33 and 7p12.2 where the MYTL1, IL12A and IKZF1 genes are located, respectively. Conclusions: Our results show that the comparative use of two populations provides clues on the diversity and the history of the genetic susceptibility behind a complex disease such as RA. References: Kim, K. et al. Ann. Rheum. Dis. (2014). doi:10.1136/annrheumdis-2013-204749 Jia, X. et al. PloS One 8, e64683 (2013). Raychaudhuri, S. et al. Nat. Genet. 44, 291–296 (2012). Acknowledgements: This work was supported by the followuing grants: Instituto de Salud Carlos III (ISCIII) from Spanish Health Ministry RETICS Program RD12/0009 and PI12/02558, the C2A Andalusian recruitment program from Junta de Andalucía (Spain), the European IMI BTCure Program and the Swedish Research Council. MT is supported by the Instituto de Salud Carlos III (Spanish Health Ministry), through the Sara Borrell subprogram [CD13/00316]. Disclosure of Interest: None declared